Reduction in Acidity of RDX and its Compositions by Use of Suitable Additives - Singh, Harihar; Seshadri, N. M.; Singh, Surjit (Defence Science Journal, 2014)
Calcium Silicate and Zinc Stearate have been used as additives to reduce the acidity of RDX and RDX/TNT compositions. They have been found to be effective in reducing the acidity of RDX/TNT compositions but ineffective for RDX alone. An explanation to this effect has been provided.